2012
DOI: 10.2139/ssrn.2194792
|View full text |Cite
|
Sign up to set email alerts
|

Rational Speculators, Contrarians and Excess Volatility

Abstract: The VAR approach for testing present value models is applied to a nonlinear asset pricing model with three types of agents, using historical US stock prices and dividends. Besides rational long-term investors, that value assets according to expected dividends, the model includes rational and contrarian speculators. Agents choose their regime based on evolutionary considerations. Supplementing the standard present value model with speculative agents dramatically improves the model's ability to replicate the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 66 publications
0
18
1
Order By: Relevance
“…Belief coe cients/A-synchronous updating ratio(? )/Intensity of choice Huisman et al (2010) A B S Q M L B e l i e f c o e c i e n t s / I n t e n s i t y o f c h o i c e Kouwenberg and Zwinkels (2014) ABS QML Belief coe cients/Intensity of choice Kouwenberg and Zwinkels (2015) ABS QML Price elasticity/Belief coe cients/Intensity of choice Lof (2012) A B S N L S B e l i e f c o e c i e n t s / I n t e n s i t y o f c h o i c e Lof (2015) ABS Duan and Simonato (1998), GMM for generalized method of moments, and SMD for simulated minimum distance. '?'…”
Section: A Route To Empirical Estimation Of Fabms: Review Of Existingmentioning
confidence: 99%
“…Belief coe cients/A-synchronous updating ratio(? )/Intensity of choice Huisman et al (2010) A B S Q M L B e l i e f c o e c i e n t s / I n t e n s i t y o f c h o i c e Kouwenberg and Zwinkels (2014) ABS QML Belief coe cients/Intensity of choice Kouwenberg and Zwinkels (2015) ABS QML Price elasticity/Belief coe cients/Intensity of choice Lof (2012) A B S N L S B e l i e f c o e c i e n t s / I n t e n s i t y o f c h o i c e Lof (2015) ABS Duan and Simonato (1998), GMM for generalized method of moments, and SMD for simulated minimum distance. '?'…”
Section: A Route To Empirical Estimation Of Fabms: Review Of Existingmentioning
confidence: 99%
“…Various versions of the model, with varying numbers and types of agents, different profit and/or switching functions, and varying results, have been estimated successfully on a large number of asset classes. Especially stock markets (Boswijk et al, 2007;Hommes and in 't Veld, 2017;Chiarella et al, 2014;Lof, 2014) and foreign exchange markets (Frankel and Froot, 1990;De Jong et al, 2010;Spronk et al, 2013) have been extensively analyzed, but the model has also showed itself useful in explaining the price dynamics in, for instance, housing markets (Kouwenberg and Zwinkels, 2014;Bolt et al, 2014), option markets (Frijns et al, 2010), commodity markets (ter Ellen and Zwinkels, 2010;Baur and Glover, 2014;Westerhoff and Reitz, 2005), and credit markets (Chiarella et al, 2015). Even macro-economic variables such as inflation can be described by a heterogeneous agent model, as in Cornea-Madeira et al (2017) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Hommes and in't Veld (2014) follow a similar approach, using both the dynamic Gordon present-discounted-value and the Campbell-Cochrane consumption habit fundamental benchmarks, using quarterly S&P500 data 1950-2013 and conclude that the financial crises has been amplified by switching between fundamentalists and trend-following strategies. Lof (2014) estimates a HAM with different VAR-model specifications to the S&P500 index and finds temporary switching between fundamentalists and rational and contrarian speculators. Lux (2009) estimated the parameters of a dynamic opinion formation process with social interactions based on survey data on business expectations (sentiment index data).…”
Section: Introductionmentioning
confidence: 99%